ANALISIS HISTORIS TENTANG SUFISME AL-GHAZĀLĪ - Salahuddin Salahuddin (Hunafa: Jurnal Studia Islamika, 2010)
Al-Gazālī is views  as a figure who succeeded to reconciled between  the Shari'a with Sufism, and it was he who succeeded to make the teaching of sufism be accepted by the fiqh ulamahis  (scholars of Fiqh). Sufism is the final  path which he chose before which he  intensely studied the sensory sciences, theology, and philosophy. It was in Sufism, according to him, that he found the true knowledge which comes from the Creator.Kata Kunci: analisis sufisme. Al-Ghazali, syariat, tasawuf